Investigations of the physico-chemical behaviour of starch-water systems : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology at Massey University - Wong, Richard Bek Kiong (Massey University, 1981)
Starch is a major component of many of the world's food supplies. In order to utilise these supplies effectively the properties of starch must be fully understood. Although starch systems have been investigated quite extensively, there is relatively little information concerning the physico-chemical behaviour of starch under conditions relevant to food processing. The texture of many fabricated foodstuffs is regulated by adding starch. In many cases the addition of starch causes food systems to behave as viscoelastic pastes. In Australasia, wheat starches are generally used to control texture. However starches from some wheat cultivars do not impart the desired rheological characteristics to foodstuffs and this thesis concerns an investigation into this phenomenon which was investigated in three sections. In section I, a fundamental study of the rheological properties of wheat starch pastes was performed. Measurements were made of the flow behaviour of pastes under both oscillatory and steady shear conditions. Pastes formed under a range of experimental conditions from various wheat varieties were studied. Both wheat varieties and paste preparation conditions were found to influence rheological behaviour. The results show that differences in the pasting properties of starch pastes may be attributed to two factors, namely the swelling capacity of the starch (the volume which the starch gel particles would occupy when close packed if excess solvent were present) and the size distribution of the granules. The rheological properties depend on the source of starch since this effects particle swelling capacities and size distributions. Paste preparation conditions influence rheological properties since they alter the volume occupied by gelatinised granules. The rheological behaviour of starch pastes changes with time when the pastes are stored. The effect of storage on dynamic rigidity was investigated and the results suggested that a crystallisation process is responsible for the increase in dynamic rigidity with time. The results were therefore evaluated using the Avrami equation. In section II, an investigation was made of the degree of crystallinity, that is the proportion of polymer chains that are in an ordered state, in a number of wheat starch varieties that have different swelling capacities. Measurements of the X-ray crystallinity index, enthalpy change and specific volume were used to investigate crystallinity. The results show that higher swelling capacities are associated with relatively disordered arrangements of polymer chains within granules. The crystallinity results for the various starch fractions with narrow size ranges confirm previous studies showing that small granules tend to be more crystalline. However small granules were found to have higher swelling capacities than large granules. In this instance the increased swelling capacity of small granules as compared to large is probably due to the decreased amount of lipid per unit area at the surface of the small particles. In section III, Proton (1H) and Carbon-13 (13C) NMR were used to investigate starch pastes made from different wheat varieties that have different pasting properties. 1H spin-lattice (T1) relaxation times, 1H spin-spin (T2) relaxation times, polymer hydration coefficients (h) and 1H diffusion coefficients (D) of starch-water systems were determined. Line-widths at half-heights (Δ√1/2) of peak intensities at various carbon positions and total 13C liquid signals were also obtained. In all cases the NMR parameters were not found to be dependent on wheat variety. The polymer hydration coefficient, that is the amount of water molecules that are in the bound state, was estimated from the ratio of the amplitude of the 1H signal due to unfrozen water at 258K to the amplitude of the 1H signal at 303K. A value of 0.34 gH2O/g dry starch was obtained. The T1 and T2 magnetisation recovery curves for starch pastes were found to be single exponential functions. This suggests a fast molecular exchange of water molecules between different sites in the system. A two-state model based on exchange between bulk and bound water was shown to be adequate in describing the relaxation behaviour of water protons in the system. Diffusion measurements of water molecules show that there is no restricted or barrier limited diffusion occuring in starch pastes. The diffusion coefficients were interpreted using various models. The best model was found to be one which takes into account both the obstruction and hydration effects. This gives a shape factor for the suspended gel particles which indicates that water is diffusing through oblate ellipsoids. These are probably amylopectin molecules present in the starch pastes. In an attempt to confirm this possibility, 1H NMR measurements were repeated on a pure amylopectin-water system. The diffusion coefficients of the amylopectin-water system were interpreted using the same model and similar result was obtained for the shape factor of amylopectin molecules. The 13C liquid signal results confirm that sharp resonances, which correspond to liquid-like behaviour on the NMR time-scale of the polysaccharide chains, are only observed when the starch is gelatinised. The decrease in the line-widths at half heights of the peak resonances at various carbon positions when the pasting temperature is increased is probably due to an increase in mobility of the polymer chains. In the various wheat starch pastes studied, a loss of about one-third of the total 13C liquid signal was observed. This was attributed to the crystallisation of polymeric material, lipid-amylose complexes and remnants of ordered structures in the starch pastes.
Keywords: Starch; Starch properties